Prevalence of and factors associated with non-partner rape perpetration: findings from the UN Multi-country Cross-sectional Study on Men and Violence in Asia and the Pacific - Prof. Rachel Jewkes, MBBS MD; Emma Fulu, PhD; Tim Roselli, BSc; Claudia Garcia-Moreno, MD (Elsevier, 2013)
Background: Rape perpetration is under-researched. In this study, we aimed to describe the prevalence of, and factors associated with, male perpetration of rape of non-partner women and of men, and the reasons for rape, from nine sites in Asia and the Pacific across six countries: Bangladesh, China, Cambodia, Indonesia, Papua New Guinea, and Sri Lanka. Methods: In this cross-sectional study, undertaken in January 2011-December 2012, for each site we chose a multistage representative sample of households and interviewed one man aged 18-49 years from each. Men self-completed questions about rape perpetration. We present multinomial regression models of factors associated with single and multiple perpetrator rape and multivariable logistic regression models of factors associated with perpetration of male rape with population-attributable fractions. Findings: We interviewed 10 178 men in our study (815-1812 per site). The prevalence of non-partner single perpetrator rape varied between 2·5% (28/1131; rural Bangladesh) and 26·6% (225/846; Bougainville, Papua New Guinea), multiple perpetrator rape between 1·4% (18/1246; urban Bangladesh) and 14·1% (119/846; Bougainville, Papua New Guinea), and male rape between 1·5% (13/880; Jayapura, Indonesia) and 7·7% (65/850; Bougainville, Papua New Guinea). 57·5% (587/1022) of men who raped a non-partner committed their first rape as teenagers. Frequent reasons for rape were sexual entitlement (666/909; 73·3%, 95% CI 70·3-76·0), seeking of entertainment (541/921; 58·7%, 55·0-62·4), and as a punishment (343/905; 37·9%, 34·5-41·4). Alcohol was a factor in 249 of 921 cases (27·0%, 95% CI 24·2-30·1). Associated factors included poverty, personal history of victimisation (especially in childhood), low empathy, alcohol misuse, masculinities emphasising heterosexual performance, dominance over women, and participation in gangs and related activities. Only 443 of 1933 men (22·9%, 95% CI 20·7-25·3) who had committed rape had ever been sent to prison for any period. Interpretation: Rape perpetration committed by men is quite frequent in the general population in the countries studied, as it is in other countries where similar research has been undertaken, such as South Africa. Prevention of rape is essential, and interventions must focus on childhood and adolescence, and address culturally rooted male gender socialisation and power relations, abuse in childhood, and poverty. Funding: Partners for Prevention-a UN Development Programme, UN Population Fund, UN Women, and UN Volunteers regional joint programme for gender-based violence prevention in Asia and the Pacific; UN Population Fund Bangladesh and China; UN Women Cambodia and Indonesia; United Nations Development Programme in Papua New Guinea and Pacific Centre; and the Governments of Australia, the UK, Norway, and Sweden.